Analisis Obesitas pada Anak Sekolah Dasar Berdasarkan Pengetahuan, Sikap, dan Paparan Informasi tentang Gizi Seimbang - Miftahul Jannah; Indah Kusumaningrum (Puslitbang Sinergis Asa Professional, 2021)
Prevalence of obesity among school children aged 5-12 years old in Jakarta is remainly high, namely 14%. Indonesia Balance Nutrition Guideline (PGS) need to be applied everyday to tackle obesity. However, the exposure to PGS information, knowledge and attitude related to PGS among school children is still lacking. This study aims to identify the association between exposure to information, knowledge, and attitudes of PGS with obesity status among school children at SD Negeri Pulogebang 11 Pagi, East Jakarta. This is a quantitative study with a cross-sectional study design. This study was conducted in SDN Pulogebang 11 Pagi with a sample of 100 fourth-grade students. Variable in this study were exposure to information, knowledge, attitudes related PGS, and obesity status. Exposure to information, knowledge, and attitudes related PGS were taken by filling out the questionnaires by respondents. Obesity status was measured by measuring height and weight. Data was analyzed by using Fisher Exact test and Chi Square test. This study shows that the prevalence of obesity is 14%. School children who had never been exposed to PGS information were 34%. School children with ≤ median score of knowledge and attitudes were 61% and 58%. Other result shows that there was no significant association between exposure to information (p = 0.371), knowledge (p = 0.363), and PGS attitude (p = 0.513) with obesity status. Other factors, such as the role of parents, peers, and school, may influence children's behavior, as in eating behavior, physical activity, and lifestyle. The conclusion of this study is the prevalence of obesity is still high. To overcome this, intervention is not only carried out among school children, but also interventions related to PGS among parents and integration with school programs are needed.